2017
DOI: 10.1063/1.4996453
|View full text |Cite
|
Sign up to set email alerts
|

Internal stress and opto-electronic properties of ZnO thin films deposited by reactive sputtering in various oxygen partial pressures

Abstract: In this article, we propose ZnO thin films as a suitable material for piezoresistors in transparent and flexible electronics. ZnO thin films have been deposited by DC reactive magnetron sputtering at room temperature at various oxygen partial pressures. All the films have a wurtzite structure with a strong (0002) texture measured by XRD and are almost stoichiometric as measured by inductively coupled plasma optical emission spectroscopy. The effect of oxygen concentration on grain growth has been studied by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Below, Table 3 summarizes the parameters and results of work reported on ZnO piezoresistive thin films and those of our proposed work. According to the work reported by Cardoso et al [19] and Tuyaerts et al [29], the piezoresistive effect of polycrystalline ZnO thin films is related to the intensity of the preferential orientation (002), where the c-axis of the wurtzite structure is perpendicular to the substrate surface. In addition to this, Cardoso et al [15] observed that increasing the Al doping of ZnO films shifted the (002) preferential orientation to higher 2θ positions, causing a decrease in piezoresistive sensitivity as well as changes in the crystal lattice.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Below, Table 3 summarizes the parameters and results of work reported on ZnO piezoresistive thin films and those of our proposed work. According to the work reported by Cardoso et al [19] and Tuyaerts et al [29], the piezoresistive effect of polycrystalline ZnO thin films is related to the intensity of the preferential orientation (002), where the c-axis of the wurtzite structure is perpendicular to the substrate surface. In addition to this, Cardoso et al [15] observed that increasing the Al doping of ZnO films shifted the (002) preferential orientation to higher 2θ positions, causing a decrease in piezoresistive sensitivity as well as changes in the crystal lattice.…”
Section: Resultsmentioning
confidence: 97%
“…The piezoresistors obtained a gauge factor of 2.6 [19]. In the study by Tuyaerts et al, a gauge factor value between −5.8 and −8.5 was reported in ZnO films obtained using DC reactive magnetron sputtering [29].…”
Section: Introductionmentioning
confidence: 89%
“…The internal stress was measured in-situ using a high-resolution curvature measurement setup aimed at the substrate in the deposition chamber [17]. Using multiple laser beams directed towards the deposited film, the curvature of the film can be quantified based on the position of the reflected beams [22].…”
Section: Methodsmentioning
confidence: 99%